Hubungan Pengetahuan Keluarga Tentang Perokok Pasif Dengan Kejadian Infeksi Saluran Pernafasan Pada Balita Di Wilayah Kerja Puskesmas Langsa Lama Tahun 2020 - Nova Radiani Br Hsb; Vivi Wulandari (Jurnal Kesehatan dan Fisioterapi, 2021)
Acute Respiratory Infection (ARI) is an acute infection process lasting for 14 days, caused by microorganisms and attacks one part, and or more of the respiratory tract, from the nose (upper tract) to the alveoli (lower tract), including adnexal tissue., such as sinuses, middle ear cavity and pleura (Erliani 2012). This study aims to determine the relationship between passive smoking and the incidence of respiratory tract infections (ARI) in children under five in the working area of the Langsa Lama Health Center, Langsa City, Aceh Province in 2020. This study was descriptive using primary data with a total sample of 40 children under five in passive smoking. with the incidence of Respiratory Tract Infections (ARI) in the Work Area of the Langsa Lama Health Center, Langsa City, Aceh Province. The results of this study indicate that the level of knowledge of children under five from 40 respondents (100%) the majority of respondents have less knowledge as many as 24 respondents (60%) and a minority of respondents with sufficient knowledge as many as 12 respondents (30%). Based on the data analysis, the results of the chi-square test at a 90% confidence level resulted in a P-Value of 0.001 (P <0.05) where Ha was accepted and Ho was rejected. This shows that statistically there is a relationship between passive smoking and ARI. This result is due to the fact that the knowledge of children under five affects the incidence of ARI. It is recommended for active smokers not to smoke near children under five because of the dangers and it is better for active smokers to stop smoking for the health of themselves, their families, and the environment.Keywords: Knowledge, Passive smokers, Infection, Respiratory, Childhood.